2015
DOI: 10.1007/s10458-015-9317-1
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating with other minds: the role of recursive theory of mind in negotiation with incomplete information

Abstract: Theory of mind refers to the ability to reason explicitly about unobservable mental content of others, such as beliefs, goals, and intentions. People often use this ability to understand the behavior of others as well as to predict future behavior. People even take this ability a step further, and use higher-order theory of mind by reasoning about the way others make use of theory of mind and in turn attribute mental states to different agents. One of the possible explanations for the emergence of the cognitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 62 publications
0
52
0
Order By: Relevance
“…But do people really use it? De Weerd and colleagues [48] showed that, by letting people play unknowingly against a second-order theory of mind agent in a repeated negotiation game, people are enticed to apply second-order theory of mind, which became much more prevalent than when the participants played against zero-order or first-order agents.…”
Section: Considering the Opponent's Perspectivementioning
confidence: 99%
“…But do people really use it? De Weerd and colleagues [48] showed that, by letting people play unknowingly against a second-order theory of mind agent in a repeated negotiation game, people are enticed to apply second-order theory of mind, which became much more prevalent than when the participants played against zero-order or first-order agents.…”
Section: Considering the Opponent's Perspectivementioning
confidence: 99%
“…In strategic games, participants are typically found to rely on low orders of theory of mind, and to be slow to adjust their level of theory of mind reasoning to more sophisticated opponents [11,3,32,10]. Earlier empirical research suggests that the use of first-order and secondorder theory of mind in games can be facilitated by creating a believable story or insightful visual representation around an abstract problem [5], by creating a clear competition or negotiation setting [10,31], or by providing stepwise training from games that require zero-order ToM to second-order ToM games, as we did in [25].…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
“…Many social skills vitally depend on the ability of the person to reason about others as goal-oriented agents with their own beliefs, goals, and intentions, an important part of social cognition. This ability to reason explicitly about unobservable mental content of others, known as theory of mind [20], has been associated with pro-social behavior [13], social competences [15], and negotiation skills [31], as well as in producing and interpreting prosody [4] and nonverbal communication through body language and gestures [18,19]. But while adults show impressive theory of mind abilities in some experiments that rely on communication, people are typically slow to take advantage of their theory of mind ability in strategic settings [11,3,32,10].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to experiments with humans, some research pitted artificial recursive reasoning agents against each other to see what reasoning depths are most useful. For example, de Weerd et al (2017de Weerd et al ( , 2013 test their specific agents in domains such as repeated rock-paper-scissors and sequential negotiation, and find that reasoning levels deeper than 2 do not provide significant benefits in their setting.…”
Section: Recursive Reasoningmentioning
confidence: 99%